A PRELIMINARY STUDY ON THE EXTRAVASATION OF INTRAVENOUS CHEMOTHERAPY IN SANGLAH GENERAL HOSPITAL, BALI – INDONESIA - Inge Kurniawati; Putu Anda Tusta Adiputra (Neurologico Spinale Medico Chirurgico, 2018)
Background: Extravasation of intravenous chemotherapeutic agents is one of the most devastating complications, which unacceptable condition neither to patient nor to medical services. Many healthcare providers realize that even one extravasation injury is too many since this injury is preventable. Published incidence rates of chemotherapy extravasation range from 0,01% to 6%, but in our institution, chemotherapy extravasation was not well recorded, so the incidencerate is unclear and the number of injuries is underestimated. Method: We observed chemotherapy extravasation occurrence during a 6 months period in our institution, from September 2013 until March 2014. We recorded the chemotherapy agents, patient’s clinical presentations, and extravasation management. Result: During our observation, 1374 chemotherapies administered, and 10 cases of chemotherapy extravasation occur, particularly doxorubicine was the main chemotherapy agent. Almost all treated conservatively, only 10% handled with surgical management. Eventually, 20% of cases have implanted port placed. Conclusion: Extravasation of cytotoxic agents is a serious problem, it causes tissue damage, prolongs the length of stay, increases hospital cost and psychological damage to cancer patients who under chemotherapy. It preventable but always underestimate by some clinicians, the use of central venous access device is one of the solutions to minimize the damage.